Long-term volatility shapes the stock market's sensitivity to news - Christian Conrad; Julius Schölkopf; Nikoleta Tushteva (University of Heidelberg, Department of Economics, 2023)
We show that the S&P 500's instantaneous response to surprises in U.S. macroeconomic announcements depends on the level of long-term stock market volatility. When long-term volatility is high, stock returns are more sensitive to news, and there is a pronounced asymmetry in the response to good and bad news. We explain this by combining the Campbell-Shiller log-linear present value framework with a two-component volatility model for the conditional variance of cash flow news and allowing for volatility feedback. In our model, innovations to the long-term volatility component are the most important driver of discount rate news. Large announcement surprises lead to upward revisions in future required returns, which dampens/amplifies the effect of good/bad news.
urn:nbn:de:bsz:16-heidok-341022
Keywords: C58; E44; G12; G14; 330; event study; long- and short-term volatility; macroeconomic announcements; stock market response; time-varying risk premia; volatility feedback effect